Green Digitalization for Smart Mobility and Low-Carbon Transportation in East Kalimantan - M. Arib Herzi Syahputra; Rusdi Rusdi; Rahma Handaya; Enos Paselle (Dinasti Publisher, 2025)
This research examines the application of the smart mobility concept as a transition strategy towards low-carbon transportation in East Kalimantan, focusing on the cities of Samarinda and Balikpapan. This research aims to analyze the role of transportation digitalization in improving public service efficiency, reducing carbon emissions, and identifying barriers to implementation. The method used is an exploratory case study with a content analysis approach to secondary data. The results show that smart mobility in East Kalimantan is beginning to have a positive impact. E-parking services, the development of e-ticketing, and the use of navigation applications have proven effective in reducing congestion and fuel consumption. Furthermore, the adoption of electric vehicles (EVs) has shown a significant increase, marked by a 452% increase in electricity consumption and a 406% increase in SPKLU (Public EV Charging Station) transactions by 2024. The expansion of SPKLU and SPBKLU infrastructure has strengthened the electric vehicle ecosystem in this region. However, obstacles remain, such as a digital literacy gap among the community, particularly among the elderly, low-income groups, and residents in rural areas. This limits the optimal utilization of digital transportation services.